Darkness-Based Synchronization Protocols: Harnessing Superluminal Frontiers (Global Journal of Science Frontier Research, 2025)
This paper investigates the propagation speed of darkness, redefined not as an absence of light but as a physical boundary whose dynamics extend the limits of illumination causality. Using wave front level-set theory, geometric projection analysis, and a reinterpretation of spacetime geometry, we derive a generalized expression for the darkness-front velocity and demonstrate that it can exceed the vacuum speed of light c = 299,792,458 m/s. We present a unified formulation, discuss the non-material nature of this boundary, and propose experimental methods to test these effects. The conclusion is reached that darkness, as a non-material but ontologically significant boundary, can propagate faster than any finite physical velocity without violating relativistic causality.
Keywords: geometric projection analysis; finite physical velocity without violating relativistic causality